Обгрунтування параметрів і режимів роботи пристрою для прокладання зрошувачів плодових насаджень - Хайдер, Аль-Хазаали Раад Надим (НУБіП України, 2017)
Дисертація на здобуття наукового ступеню кандидата технічних наук зі спеціальності 05.05.11. «Машини та засоби механізації сільськогосподарського виробництва». – Національний університет біоресурсів і природокористування України, Київ, 2017. У дисертаційній роботі виконано аналіз сучасного стану та перспектив розвитку існуючих способів та технічних засобів, параметрів і режимів їхньої роботи для зрошення сільськогосподарських культур; проаналізовано результати досліджень умов застосування системи підґрунтового зрошення; вивчено закономірності пересування й розподілу вологи в активному шарі ґрунту за підґрунтового зрошення; проаналізовано умови фільтраційного руху води для поливу та можливості його зниження. Проведено аналіз способів та технічних засобів для прокладання системи підґрунтового зрошення з застосуванням протифільтраційного екрану, що дозволяє зменшити вплив гравітаційного переносу вологи та підвищити дифузійний її перенос. Виконано аналіз літературних джерел по методам формалізації ґрунту та розв’язанню задач взаємодії робочих органів із ґрунтом. Проведений аналіз показав, що найбільш раціональним є прокладання системи підґрунтового зрошення безтраншейним способом з одночасним укладанням протифільтраційного екрану. При формалізації ґрунту доцільно використовувати модель квазісуцільного деформівного середовища з властивостями пружності та в’язкості. Для визначення раціональних параметрів і режимів роботи робочих органів необхідно розв’язати контактні задачі взаємодії абсолютно твердої поверхні робочого органу з деформівним середовищем. Розглянуті вихідні рівняння формалізації ґрунту як суцільного деформівного середовища з властивостями пружності та в’язкості у просторовій постановці. Розв’язання контактних задач взаємодії робочих органів з ґрунтом із використанням фізичних рівнянь зв’язку компонент напружень з компонентами швидкостей деформацій дозволило встановити вплив геометричних параметрів та режимів роботи робочого органу та механічних властивостей ґрунту на зміни компонент швидкостей його переміщень, швидкостей деформацій, а також змін компонент напружень у ґрунті. Отримані залежності дозволили визначити функціональні зв’язки параметрів та режимів роботи робочого органу, а також механічних властивостей ґрунту на зміни його щільності в зоні контакту з робочим органом
The dissertation on competition of scientific degree of candidate of technical sciences, specialty 05.05.11. Machines and Means of Mechanization of agricultural production. – National University of Life and Environmental Sciences of Ukraine, Kiev, 2017. In this thesis the analysis of the current state and prospects of development of existing methods and technical means of parameters and their modes of operation for irrigation of agricultural crops; examine the results of the research applications system subsurface irrigation; studied the patterns of movement and distribution of moisture in the active soil layer for subsurface irrigation; analysis of conditions of a filtration of water movement for irrigation and decrease. The evaluation of the methods and technical means for the strip system subsurface irrigation with the use of anti-filtration screen, which allows to reduce the influence of the gravitational migration of moisture and enhance its diffusion transfer. The analysis of the literature on methods of formalization of the soil and solution of problems of interaction of tools with soil. The analysis showed that the most efficient is the laying system subsurface irrigation trenchless method with the simultaneous laying of impervious screen. With the formalization of the soil, it is advisable to use the model quasi-continuous a deformable medium with the properties of elasticity and viscosity. For determination of rational parameters and operation modes of the tools is necessary to solve the contact problem of interaction of absolutely hard surface of the tool with the deforming medium. The original equations of the formalization of the soil as a continuous deformable medium with the properties of elasticity and viscosity in a spatial setting. Solution of contact problems of interaction of tools with soil using physical equations of the component stresses with the components of the strain rate has allowed to establish the influence of geometrical parameters and modes of the tool and mechanical soil properties to changes in the component velocities of its displacements, velocities, deformations, and changes in the component stresses in the soil. The dependences allowed us to determine the functional relationship of parameters and modes of the tool and mechanical soil properties to changes in density in the zone of contact with the tool. To analyze the stability of the arch was used the formalization of the soil as free-flowing discrete medium, which is a special case of the theory of plasticity, because the soil in the process of interaction with the tool is experiencing plastic deformations. This analysis using the failure criterion of Coulomb-Mohr showed the impact of connection parameters and modes of the tool to the mechanical properties of the soil on the possible formation of a stable arch that should ensure easy pulling of impervious screen together with the irrigation pipe. In this dissertation analyzed the optimal methods of laying subsurface irrigation systems are allowed to determine the rational technical solution to create them. Solved problems related to finding of rational parameters and operation modes of the tool for trenchless laying of irrigation pipes along with anti-filtration screen. Analysis of the results of studies on the propagation of liquid in the soil under the threat of salinization of the soil and in conditions of high moisture evaporation from the soil surface allowed to make a conclusion about the most rational method of the creation of irrigation network. Thus, on the basis of the analysis subsurface irrigation can be concluded that sprinklers for perennial fruit plantings can be placed in increments of up to 2 meters to a depth of 0.5 meters. The results of studying laws of movement of moisture in the soil when subsurface irrigation allow us to conclude that the greatest distribution of moisture in the perpendicular direction from the axis of the sprinkler will be provided by diffusion transfer of moisture at the lowest possible filtration processes that occur during full water saturation. This requires the use of impervious screen. Analysis of methods of laying subsurface irrigation systems with protein the screen allowed us to conclude about the absence of technical means for performing such operations trenchless method. The most appropriate from the point of view of formalizing the interaction of the working body for trenchless laying of irrigation pipes along with anti-filtration screen, is a representation of the soil as quasi-continuous isotropic medium with the properties of elasticity and viscosity. Based on the decision of contact problems of interaction of the conical part of the tool is determined by its rational geometric parameters that, to the maximum extent of the seal walls formed of the cavity and provide a minimum soil resistance to its movement. Thus, for most of the soil mechanical characteristics are such the most rational geometrical parameters of the conical part of the tool: the acute a 0.02, the base radius of the cone 1.1 t r , where t r – the radius of the tube of the sprinkler at a speed of 1 / m V м с. Based on the decision of contact problems of interaction of the share mole plow is determined by its rational geometric parameters that, to the maximum extent of the seal walls formed of the cavity and provide a minimum soil resistance to its movement. For most of the soil mechanical characteristics, the most rational geometrical parameters of the share mole plow on will be such: shingles can be made in the form of a plane with the lowest possible coefficients of slopes of the surface normal to the coordinate axes: oy – b 1, oz – c 1, ox – a2 and the geometric size of share mole plow should exceed napustio impervious screen (0.25 m), the height of the projection of share mole plow in a vertically transverse plane in the zone of contact with the cone part is the value 1.1 t r . As a result of theoretical researches the analytical dependence of the resistance of soil to movement of the tool, which depend on the geometric parameters of the tool, the speed of movement and mechanical properties of the soil. Analyzing the values of critical stresses Kkr in the upper part of the cavity formed by share mole plow created by the weight of the wedge of soil above the cavity, and the critical stresses 1 k are created in the upper part of the cavity by the share mole plow in its various settings and properties of the soil, it can be concluded that the upper part of the cavity is resistant to destruction and should not prevent to pulling of impervious screen. Comparison of the obtained theoretical dependences of the resistance to movement of the tool in the soil and resistance to pulling of the irrigation pipe along with impervious screen with the results of experimental studies on 2 types of soils allows to judge the adequacy of the theoretical results on statistical significance level 0.25.
Keywords: робочий орган; конусна частина робочого органу; лемішна частина робочого органу; формалізація ґрунту; контактна задача взаємодії; в’язко-пружна модель формалізації; сипуче дискретне середовище; утворення склепіння; сили опору пересуванню; working tool; conical part of the working tool; ploughshare part of the working tool; soil formalisation